FAKTOR YANG BERPENGARUH TERHADAP KEPATHUAN WAJIB PAJAK DALAM MEMBAYAR PAJAK - Rosita Adi Lestari, 08.05.52.0178; Badjuri, Achmad (Students Journal of Accounting and Banking, 2012)
The purpose of this study is to examine the effect of knowledge and understanding of taxation, fines penalties, tax authoritiesâ service and taxation awareness toward taxpayer compliance.The populations in this study were individual taxpayers registered in the KPP Candisari in 2011. Researchers used Accidental Sampling as a sampling method. Determination of sample in this study was determined using the Slovin formula. Primary data collection method used in this study was questionnaire. The techique of multiple regression analysis was used as a data analysis technique.Based on the results of the testing had been done, the conclusions were the variables that influence taxpayer compliance is knowledge and understanding of taxation, service tax authorities and awareness of the tax payers, while the financial penalties have no effect on taxpayer compliance.Keywords: Compliance with the taxpayer, knowledge and understanding of taxation, financial penalties, the service taxauthorities, tax awareness.